Cultural Aspects Affecting Management of the Mexican Workforce in the Czech Republic - Horálková, Kristýna; Martínez Pantoja, Yadira Ixchel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2026)
This thesis explores how cultural differences between Mexico and the Czech Republic influence workplace dynamics and management practices. It focuses on how cultural differences shape the way people communicate, interact, form expectations and adjust to a new work environment. The theoretical part is based on intercultural management literature, cultural dimension models and an overview of Mexico. The practical part uses qualitative interviews with Mexican workers living and working in the Czech Republic and was analyzed using thematic analysis to identify recurring patterns. The findings suggest that cultural differences significantly influence workplace expectations and cooperation and highlight the importance of intercultural understanding. The thesis offers practical recommendations for Czech managers to support effective management and successful integration of Mexican employees in the Czech work environment.
Vedoucí práce: Yadira Ixchel Martínez Pantoja
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses